Analysis and information content of quadrupolar NMR in glasses: 25Mg NMR in vitreous MgSiO3 and CaMgSi2O6 - Marcos de Oliveira, Jr.; Hugo Damasceno; Philip S. Salmon; Hellmut Eckert (Journal of Magnetic Resonance Open, 2022)
The static wideline and high-resolution magic angle spinning (MAS) 25Mg NMR lineshapes measured for isotopically enriched enstatite and diopside glasses indicate a wide distribution of the electric-field gradient (EFG) components at the 25Mg position caused by disorder. The correct characterization of this distribution requires simulations with special attention paid to the experimental parameters. Here, both the static spectra obtained by wideband excitation and the MAS-NMR spectra obtained via rotor-synchronized Hahn spin echo acquisition were successfully simulated with the Czjzek distribution model, using one consistent set of parameters. Average nuclear electric quadrupole coupling constants near 8 MHz and a distribution width around 4 MHz were obtained for both materials, which suggests that earlier results on these glasses need to be re-examined. The results of this study outline a general strategy for characterizing the local environments of strongly coupled quadrupolar nuclei in amorphous and glassy materials. Despite the discrepancies between the interaction parameters extracted from our data and those published in earlier NMR work, the best fit to the data indicate an average isotropic chemical shift near 13 ppm (vs. aqueous MgCl2 solution) for both the enstatite and diopside glasses. Assuming the applicability of the current database relating the 25Mg chemical shifts with coordination numbers in crystalline compounds, this value suggests that the Mg2+ ions are six-coordinated. This conclusion, however, is based on the simplifying assumption that the 25Mg spectrum comprises a Czjzek distribution centered at a single isotropic chemical shift value and stands in contrast to the results of recent isotope-selective neutron diffraction studies which give an average Mg-O coordination number of 4.4–4.5 for both glasses. However, reasonable fits to the MAS-NMR spectra can also be obtained when constraining the average isotropic chemical shift to 50 ppm, a value typical of four-coordinated Mg. We conclude that multiple Mg sites with different coordination numbers may well be present and that, in the present glasses, 25Mg NMR at typically used spinning rates and magnetic field strengths (20 kHz, 14.1 T) is not capable of resolving them due to excessive broadening by quadrupolar interactions.